40세 이상 성인의 정신건강과 구강건강관련 삶의 질의 관계에서 치주건강의 매개효과 - 김소희; So-hee Kim; 배성숙; Sung-suk Bae; 강민경; Min-kyung Kang; 정나래; Na-rae Jeong; 이미라; Mi-ra Lee (Han'guk Ch'iwisaeng Hakhoe chi, 2024)
Objectives: In this study, we investigated the mediating effect of periodontal health on the relationship between mental health and oral health-related quality of life in adults aged 40 years or older. Methods: This study was conducted from June 3 to July 24, 2024. We analyzed the data of 339 adults aged 40 years or older statistically. Multiple regression analysis was conducted according to a three-step procedure to determine the mediating effect of periodontal health on the influence of mental health on oral health-related quality of life. Results: In Model I, depression had a statistically significant effect on periodontal health. In Model II, depression and cognitive function were statistically significant factors in the OHIP-14 scores. In Model III, periodontal health was a statistically significant factor in the OHIP-14 scores. In addition, periodontal health had a complete mediating effect on the relationship between depression and OHIP-14 scores. Conclusions: Depression and periodontal health are directly or indirectly related to the quality of life of adults aged 40 years and older. Therefore, ways to improve the mental and oral health of adults should be identified, in order to improve their quality of life after middle age.